Stress Management of Therapists in Dealing with Children with Autism Spectrum Disorder (ASD) Who are Exposed to Gadgets in the Digital Era - Anita Reviana; Farida Yuliaty; Taufan Nugroho (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
In the era of globalisation, the use of gadgets has increased rapidly, including among children, bringing both positive and negative impacts. In children with Autism Spectrum Disorder (ASD), gadgets trigger aggression, reduce focus, and lead to repetitive behaviours, stimming, and babbling, making them a challenge for therapists. This study aims to analyse therapists' stress management in handling children with ASD who are exposed to gadgets. Using a descriptive qualitative approach with four informants through interviews, observations, and documentation, the data were analysed using NVivo 12. The results show that therapists manage stress through relaxation, emotional release, and mindfulness, which are generally effective in preventing burnout, although there are differences in satisfaction among the informants.